Análise do efeito do escoamento recíproco em queimador poroso volumétrico - Araújo, Welkson Carneiro de (2016)
This dissertation consists of a theoretical-experimental study, based on the fundamentals of Combustion in Porous Media technology, about the effect of reciprocal flow on the performance of a volumetric burner when compared in the unidirectional flow condition. This technology has attracted attention of combustion experts as to its application in renewable energy in the academic and business areas due to the possibility of burning low calorific fuels, associated with increased flammability range of air-fuel mixture, obtaining very low greenhouse gas emissions. In this study, it was used an experimental apparatus composed of a porous burner consisting of alumina spheres (Al2O3), a reversing the flow of gases system, a monitoring system and a data acquisition system and a analysis system of NOx and CO. The experiments were conducted in a wide equivalence ratio range (0,1 ≤ Φ ≥0,9) and gas flow velocity (0,1≤ vg ≥0,3) . From experimental data on temperature profiles, emissions and efficiency and, through the classical concepts of excess enthalpy and theoretical models for calculating temperature and emissions, a comparative analysis for both operating conditions of the porous burner was performed (unidirectional and reciprocal flow). The results showed that the use of the reciprocal flow increases the amount of recirculated heat to the cool mixture in relation to unidirectional flow condition enabling to obtain a higher reaction rate, energy extraction efficiency above 90% and ultra-low emissions of CO and NOx, 0,5 e 1 ppm, respectively. Furthermore, the heat recirculation becomes crucial for the process in ultra-low equivalence ratios (Φ ≤ 0,4) where the effect of excess enthalpy in the reaction zone may be better characterized. As a result of this larger recirculated heat, it happens a length of the fuel flammability limits, making the application of reciprocal flow markedly advantageous in this equivalence ratio range. Finally, the elements used in this research as tools for the interpretation of CMP phenomena, both the experimental apparatus and the analytical and numerical models, and the GASEQ software to calculate the chemical equilibrium, were shown to allow an analysis of the processes and of the concept of excess enthalpy with a certain consistency.